The Influence of Competence, Independence, and Professionalism on Audit Quality Mediated by Ethics (Case Study of Auditors at the Financial and Development Supervisory Agency, Papua Province Representative Office) - Gabriel Yusuf Adhi Nugroho; Paulus K. Allo Layuk; Meinarni Asnawi (urn:multiple://2988-7828multiple.v3i84)
The influence of competence, independence, and professionalism on the quality of audit results mediated by ethics (a case study of auditors at the Financial and Development Supervisory Agency (BPKP) Representative Office in Papua Province). The objectives of this study are: to examine and analyze the influence of competence, independence, professionalism, and ethics on audit quality at the BPKP Representative Office in Papua Province; to examine and analyze whether auditor ethics can mediate the influence of competence, independence, and professionalism on audit quality at the BPKP Representative Office in Papua Province. This study is a quantitative study using primary data obtained from a questionnaire measured using a Likert scale. The population in this study was BPKP auditors in Papua Province, with a total of 85 respondents. The analysis tool used was SEM with Smart PLS. The results of the study indicate that competence, independence, professionalism, and ethics simultaneously have a positive and significant effect on the quality of audit results at the BPKP Provincial Office in Papua. Ethics can mediate the influence of competence on audit quality at the BPKP Provincial Office in Papua, ethics can mediate the influence of independence on audit quality, and ethics can also mediate the relationship between professionalism and audit quality at the BPKP Provincial Office in Papua.